Low-dose valaciclovir prophylaxis against cytomegalovirus disease in renal transplant recipients. - Reddy, S; Handa, A; Tan, L; Devaney, A; Hughes, D; Mason, P; Friend, P; Darby, C (2003)
High-dose valaciclovir at up to 8 g/day has been shown to be effective in prophylaxis against cytomegalovirus (CMV) disease in renal transplant recipients. We report our experience with low-dose valaciclovir prophylaxis of up to 3 g/day, adjusted to creatinine clearance. A group of patients at high risk of developing CMV disease who received prophylaxis were selected as the study group. This included all CMV-positive patients who received antilymphocyte therapy (R+, n=20) and all CMV-negative recipients of CMV-positive organs (D+R-, n=15). D+R- patients receiving antilymphocyte therapy were excluded, as most of the patients in the control group had received ganciclovir prophylaxis. A historical control group was used, which consisted of patients who did not receive prophylaxis. Low-dose valaciclovir prophylaxis resulted in a statistically significant decrease (8.5 vs 37%, P=0.004) in CMV disease in the study group at 6 months. On subgroup analysis the decrease was statistically significant only in the R+ group (5 vs 45%, P=0.003), not in the D+R- group (13.3 vs 26.6%, P=0.651). Low-dose valaciclovir prophylaxis seems to be adequate for R+ patients receiving antilymphocyte therapy. The role of low-dose valaciclovir prophylaxis needs to be assessed further in a prospective trial.